2014
DOI: 10.3109/14767058.2014.947571
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant administration without intubation in preterm infants with respiratory distress syndrome – our experiences

Abstract: Surfactant application via a thin endotracheal catheter without intubation seems to be a beneficial therapy for preterm infants with slight and mild degree of RDS. This new method of surfactant application was associated with a lower prevalence of intubation and MV and better pulmonary outcome than implementation of traditional surfactant therapy (INSURE) and MV. Prospective randomized controlled trial is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…30 In contrast, Krajewski et al conducted a cohort study involving 26 preterm infants with RDS receiving surfactant via thin catheter and reported significant reductions in the need for mechanical ventilation (19.2% vs 65%, P < .05) and BPD (15.4% vs 40%, P < .05) compared to historical results with the INSURE technique. 31 …”
Section: Discussionmentioning
confidence: 99%
“…30 In contrast, Krajewski et al conducted a cohort study involving 26 preterm infants with RDS receiving surfactant via thin catheter and reported significant reductions in the need for mechanical ventilation (19.2% vs 65%, P < .05) and BPD (15.4% vs 40%, P < .05) compared to historical results with the INSURE technique. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Mothers had a mean age of 31.0 (16-40) years and only one of them presented an underlying medical condition (HELLP syndrome). The more frequent type of delivery was C-section (15/20, 75.0%), and the multiple birth rate was 35.0% (7/20). Only three preterm infants (15.0%) were hospitalized on the rst day of admission at the NICU, whereas the rest of neonates (17/20, 85.0%) were admitted to an intermediate neonatal care unit.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis conducted by Lau et al [32] provides a comprehensive review of the use of LISA via thin catheter in preterm infants, examining the results of several studies [14,[33][34][35]. Overall, the authors underline the suitability of this technique in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…They found significantly higher survival rates (75.8 vs. 64.1%), less IVH (28.1 vs. 45.9%), severe IVH (13.1 vs. 23.9%), and cystic periventricular leukomalacia (1.2 vs. 5.6%) in the infants treated with LISA method compared to their historical controls of invasive surfactant delivery. In a similar study, Krajewski et al (68) found that surfactant replacement therapy without intubation while receiving NCPAP in preterm infants was associated with significantly lower need for intubation and mechanical ventilation compared to the INSURE method (19.2 vs. 65%). In addition, better pulmonary outcomes were seen with the new method of surfactant replacement.…”
Section: Reviewmentioning
confidence: 91%